Dan Callahan's Press Clips - Gilbert, Susan (The Hastings Center report, 2019)
For more than eleven years, I worked with Dan Callahan as an editor, a liaison with journalists, and a sounding board for ideas. To Dan, every new writing project was a thrill, whether it was for the New Republic or a blog. He consumed a wide range of professional and scholarly literature, followed the news with the eye of a reporter, and called experts when he wanted to learn more about something he had read. The result was a volcanic bubbling of story ideas. If he didn't turn them into articles or books, I sometimes had the feeling that he might burst.